Optimalisasi Screenhouse dalam Budidaya Melon Berorientasi Agribisnis: Studi Potensi dan Pengembangan Model Pelatihan di UPT Pelatihan Pertanian Jawa Timur - Fatchur Rozci; Marsyanda Jasmine Reviyanto; Gilang Ramadan; Moh. Syauqil Umam (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Indonesian agriculture faces various challenges such as climate change, land-use conversion, and the low interest of younger generations in the sector. To address these issues, it is necessary to improve the quality of human resources through training based on modern agricultural technology. This study aims to analyze the potential use of screenhouses in agribusiness-oriented melon cultivation and to develop a training model implemented at the UPT. Pelatihan Pertanian Jawa Timur. The methods used include participatory observation and a qualitative descriptive approach, utilizing both primary and secondary data sources. The results show that screenhouses have significant potential as educational and productive facilities in enhancing the efficiency of melon cultivation through controlled growing environments, the use of technologies such as drip irrigation and direct planting systems, as well as integrated pest and disease management. In addition, the training model implemented is holistic, covering technical aspects of cultivation, agribusiness management, and digital marketing, using an andragogical approach that encourages active participant engagement. The integration of QR codes as interactive learning media further strengthens the role of technology in the training process. The optimization of screenhouses not only boosts agricultural productivity but also strengthens the capacity of young farmers to adapt and innovate in response to the dynamic future of agribusiness.